ANALISIS TEUN A. VAN DJIK DALAM KAJIAN WACANA TEKS DAKWAH DI MEDIA MASSA - Umi Halwati (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2011)
Mass media construd dakwah discourses in text forms. The texts of dakwah discourses in mass media need to be analyzed and discourse analysis can reveal the discourse of dakwah texls in mass media. The discourse analysis of Teun A. Van Djik covers: 1) text analysis, that is, how to analyze texf structures by applying linguistic analysis to explain and get the meaning of a text; 2) social cognition analysis, that is how a text was created by the author; and 3) social analysis, that is how a text is related to social strudure and knowledge of the society.